Reliability of Joint Position Sense and Force-Reproduction Measures During Internal and External Rotation of the Shoulder - Dover, Geoffrey (National Athletic Trainers' Association, Inc., 2003)
OBJECTIVE: To determine the reliability of 2 common measures of proprioception. DESIGN AND SETTING: Joint position sense (JPS) and force reproduction (FR) were measured in the dominant shoulder using internal-rotation (IR) and external-rotation (ER) target angles on 2 consecutive days. SUBJECTS: Thirty-one healthy subjects (age = 22.0 ± 2.8 years, height = 171.8 ± 9.2 cm, mass = 69.5 ± 15.9 kg) who did not regularly compete in overhand sports volunteered to participate in the study. MEASUREMENTS: Error scores were calculated at 2 target angles by averaging the absolute difference of 3 trials of JPS and FR. Reliability was determined by comparing the error scores obtained on 2 consecutive days. RESULTS: The inclinometer was found to be a reliable instrument as both intertester (.999) and intratester (.999) intraclass correlation coefficients were high. The JPS and FR measurements were also found to be reliable, with intraclass correlation coefficients ranging from .978 to .984. No differences were observed between trials for either measure. CONCLUSIONS: The inclinometer was a reliable instrument and can provide an affordable and accurate measure of range of motion and JPS. Both JPS and FR were also reliable measures of proprioception in the shoulder. Further research is needed to identify the specific mechanism of proprioception during these tasks.